Benefits management and its value to the organisation: a case study in a private organisation - Ngobeni, Ntombifuthi (Department of Construction Economics and Management, 2026)
This research evaluates the application of the Benefits Realisation Management (BRM) particularly in the private sector with strategy implementation projects. The key objectives of this study are: to evaluate the alignment of project benefits and the organisations strategic goals, to understand the processes followed to ensure the benefits identified are realised, and to further understand the challenges that the organisation may be facing that influence the adoption of BRM as well as gain insights on potential aiders that can help accelerate the adoption of BRM in the private sector. Ten senior and executive management team members voluntarily participated in the study, and most of the participants completed the interview sessions via face-to-face meetings in the Western Cape, City of Cape Town and others were interviewed online. The analysis of the data has revealed that, the organisation considers project success as the project that has met the triple constraints criteria, delivered on time, on budget and on the agreed scope which is considered to be the project management success as it is still based on the traditional approach to project management even though project success view has shifted overtime and according to literature, the project success is based on the Project Management success as well as the customer satisfaction and the value that the project change has brought about (project benefits). The organisation puts in effort at the pre-initiation phase of the project by identifying the benefits and ensuring it aligns to the strategic objectives of the organisation to obtain funding as this has become a requirement to justify projects and get the board's approval. Whilst this is the first step to the BRM process, the study reveals that the benefits identified at the beginning of the are not tracked or monitored throughout the project or post completion. Also, the findings reveal that the projects that do not require funding from the board do not necessarily have to align to the organisations strategic goals and some do not follow the project governance processes thus, the BRM process is not fully implemented. Another key finding is that the organisation still regards project success based on the traditional approach to project management, which is the project deliverable being met, on time and on budget, they confirm that the benefits realisation should be part of the project measure of success, and the view of project success needs to be based on the project value which includes the realisation of the benefits anticipated. The organisation still does not have a clear understanding of who the benefit accountability should lie with, the study reveals that there is a lack of accountability in the organisation as well as the unclarity of who is or should be accountable for benefit realisation. Although the senior management teams believe that the BRM process should be implemented in the organisation and applied across the divisions, there are gaps within the organisation which mainly includes, the education of the business on the BRM process itself, setting up the BRM process and standardising it across the departments, reinforcement of accountability, stakeholder involvement and gaining Top Management buy-in. The correction of these should then aid the adoption of the BRM process. The limitations of this research are the region and sector in which the study was conducted. The study was conducted in a single private organisation headquarter in the Western Cape region in South Africa. The organisations sector is the retail sector. Only certain departments that implement strategy driven projects were invited to participate to the study. The study can be expanded, and the recommendations are outlined in the report.